Case Report: Trochlear Wedge Sulcoplasty, Tibial Tuberosity Transposition, and Lateral Imbrication for Correction of a Traumatic Patellar Luxation in a Miniature Companion Pig: A Case Report and Visual Description - Høy-Petersen, Jennifer; Smith, Joe S.; Merkatoris, Paul T.; Black, Kelley E.; Faivre, Cosette M.; Miles, Kristina G.; Tatarniuk, Dane M.; Kraus, Karl H. (Frontiers in Veterinary Science, 2021)
The objective of this case report was to describe successful surgical and post-operative management of a medial patellar luxation in a Vietnamese Potbellied Pig. A two-year old, castrated, Vietnamese Potbellied Pig presented to a veterinary teaching hospital for right pelvic limb lameness of two weeks duration. Upon physical examination a grade 3 patellar luxation was diagnosed on the right pelvic limb. Surgical repair included a trochlear wedge sulcoplasty, tibial tuberosity transposition, and lateral imbrication as described for canine patellar luxation. The pig was managed post-operatively with meloxicam and a physical therapy regimen of seven weeks duration. At recheck examination the pig was sound, and no complications were observed. As miniature companion pigs, such as Vietnamese Potbellied Pigs are currently increasing in popularity as pets, this case demonstrated that comparative techniques from other veterinary species should be considered when considering a treatment plan for a pig with a medial patellar luxation.